2013
DOI: 10.3389/fnsys.2013.00051
|View full text |Cite
|
Sign up to set email alerts
|

The role of the anterior, mediodorsal, and parafascicular thalamus in instrumental conditioning

Abstract: The traditional animal model of instrumental behavior has focused almost exclusively on structures within the cortico-striatal network and ignored the contributions of various thalamic nuclei despite large and specific connections with each of these structures. One possible reason for this is that the thalamus has been conventionally viewed as a mediator of general processes, such as attention, arousal and movement, that are not easily separated from more cognitive aspects of instrumental behavior. Recent rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 69 publications
(121 reference statements)
7
86
0
Order By: Relevance
“…This distinction is consistent with evidence that prelimbic PFC lesions affect reinforcement devaluation when rats are lesioned before training . More recently Bradfield et al (2013) demonstrated similar impairment of reinforcement devaluation with crossed unilateral lesions of MD and prelimbic cortex (combined with a corpus callosum lesion to prevent inter-hemispheric transfer). None of these lesions affected outcome-induced reinstatement in which presentation of one of the reinforcers in extinction selectively increases responding on its associated lever Bradfield et al, 2013).…”
Section: The Mediodorsal (Md) Midline (M) and Rostral Intralaminarmentioning
confidence: 82%
“…This distinction is consistent with evidence that prelimbic PFC lesions affect reinforcement devaluation when rats are lesioned before training . More recently Bradfield et al (2013) demonstrated similar impairment of reinforcement devaluation with crossed unilateral lesions of MD and prelimbic cortex (combined with a corpus callosum lesion to prevent inter-hemispheric transfer). None of these lesions affected outcome-induced reinstatement in which presentation of one of the reinforcers in extinction selectively increases responding on its associated lever Bradfield et al, 2013).…”
Section: The Mediodorsal (Md) Midline (M) and Rostral Intralaminarmentioning
confidence: 82%
“…We purposely focussed in this review on the role of the anterior and the mediodorsal groups as those are the nuclei that received most experimental attention thus far, but it is clear that several other thalamic areas contribute to this functional heterogeneity, including the ventral midline nuclei , the intralaminar group (Lopez et al, 2009) or the parafascicular nucleus (Bradfield et al, 2013), among others. Experimental studies conducted in rodents have provided a clear functional dissociation between the anterior and the mediodorsal thalamus which is highly instructive with respect to our current understanding of diencephalic amnesia.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this role of the MD is reminiscent of that of the prelimbic part of the medial prefrontal cortex (Corbit et al, 2003;Coutureau et al, 2009;Killcross and Coutureau, 2003;Tran-Tu-Yen et al, 2009), therefore reinforcing the idea that thalamocortical interactions are necessary for the acquisition of goal-directed behaviors. A recent disconnection study indeed demonstrated that contra-but not ipsilateral lesions of the prelimbic cortex and the MD prevented adaptive response to outcome devaluation (Bradfield et al, 2013). Beyond the prelimbic cortex however, instrumental performance has been shown to also include part of the medial temporal lobe as the basolateral amygdala (BLA, Fig.…”
Section: The Mediodorsal Thalamus and Goal-directed Behaviormentioning
confidence: 98%
“…Moreover, these data are consistent with the results presented above that the thalamic relay nuclei can have somewhat different roles in behavior than the cortical areas to which they project or from which they receive input. One possible interpretation of these results is that thalamic relays are the recipient of abundant neuromodulation and are thus subject to direct control of arousal and wakefulness in a manner that differs from the cortex (Steriade et al, 1990(Steriade et al, , 1997Bayer et al, 2002;Jones, 2003;Mair et al, 2011). These modulatory changes, by affecting the excitability and efficacy of a cognitive corticothalamic or thalamocortical circuit, can have a major impact on executive function.…”
Section: Cognitive Effects Of Disrupting Thalamic Relaysmentioning
confidence: 99%
“…Recent work has demonstrated that it is also the recipient of brainstem signals related to the execution of saccades, which it passes along to oculomotor control regions of the frontal cortex (Sommer and Wurtz, 2008). Previous anatomical studies have shown that the eye movement-related layers of the superior colliculus project to lateral MD neurons (Benevento and Fallon, 1975;Harting et al, 1980), which in turn project almost exclusively to the frontal eye fields (Barbas and Mesulam, 1981;Goldman-Rakic and Porrino, 1985;Lynch et al, 1994). Sommer and Wurtz (2002) identified the most lateral edge of MD as a critical relay that transmitted signals from the superior colliculus to frontal eye fields in behaving monkeys.…”
Section: Diverse Neural Signals In the Prefrontal-projecting Thalamusmentioning
confidence: 99%